THE EFFECT OF USING MIXED WASTE ASH COMBUSTIONAS THE PARTIALLY REPLACEMENT OF FINE AGREGATE TO THE LOCKBRICK MODULAR CHARACTERISTICS - Prihatono, Yogo; Habsya, Chundakus; Sumarni, Sri (Pendidikan Teknik Bangunan, 2014)
ABSTRACTThe goal of this research to discover: the effect of using mixed waste ash combustion to partially replace fine agregate against specific gravity, compressive strength, and modular lockbrick water absorption, discover the optimal percentage of mixed waste ash combustionutilized on partial replacement of fine agregate against specific gravity, compressive strength, and modular lockbrick water absorption. Any variable work on this research is a dependent variable: specific gravity, compressive strength, and modular lockbrick water absorption, independent variable: variation of mixed waste ash combustion added with the percentage of 0%, 15%, 20% and 25% from total weight of sand. The result of this research can be concluded as: the variation of mixed waste ash combustion as partial substitute for fine agregate affect heavily in a negative way against specific gravity and compressive strength of modular lockbrick wherein decreasing the values.At the same time, the value of moduler lockbrick water absorption effect heavily in a positive way wherein causing the values to increase. The optimal values of specific gravity, compressive strength and water absorption occurs in the variation of 15% because it belongs to small amount of specific gravity and modular lockbrick type III without ignoring the values of compressive strenght and water absorption.Keyword: lockbrick modular, mixed waste ash combustion, specific gravity, compressivestrength, water absorption.